Implementation of Policy Regulation on Dengue Fever Treatment Through Gene Drive of Wolbachia Bacteria - Benny Djaja; Yuwono Prianto; Fully Handayani Ridwan; I Made Hery Karyadika; Kurniawan (Dinasti Research, 2024)
Dengue fever is an infectious disease transmitted through the bite of the Aedes aegypti mosquito. Efforts to control this disease often face insecticide resistance and environmental factors. One innovation that is expected to reduce the spread of DHF is the application of gene drive by utilizing Wolbachia bacteria. This technology works by infecting mosquito populations to reduce their ability to transmit dengue virus. This article discusses the implementation of the policy on dengue treatment through gene drive based on Wolbachia bacteria in Indonesia, focusing on regulatory aspects, field tests, and community acceptance of the technology. This study used a qualitative approach with secondary data analysis from policy documents, field trial results, and interviews with stakeholders. The results showed that although field trials showed promising results in reducing the spread of DHF, the challenges faced were immature regulations and public concerns regarding environmental and health impacts. Therefore, a more integrated policy approach is needed, as well as better communication to increase public understanding and support for this innovation.